An Exploration of Customer Perceived Value (CPV) and Characteristics of Potential Chinese Online Grocery Consumers - Wu, Yaoyao (2010)
Abstract As a well-developed industry in western countries, online grocery service is relevant new in China. Many renowned retailers attempt to launch this service in China due to the great potential of this market environment. Understanding Chinese consumers’ behaviours towards this service is significant to plan their marketing strategies. This project aims to explore the pre-purchasing customer perceived values (CPV) and characteristics of potential Chinese online grocery consumers. Ten semi-structured online interviews with assumed potential consumers are conducted. Theory of planned behaviour (TPB) is employed to classify both positive and negative perceptions, and theory of CPV is utilized to analyze the impact of each perception. Four positive perceptions or perceived benefits as well as four negative perceptions or perceived costs of potential Chinese online grocery consumers are explored, influence from reference group as a neutral element is also identified. The basic characteristics and the differences between Chinese and western online grocery consumers are investigated.